Electrocatalytic ethanol oxidation reaction: recent progress, challenges, and future prospects - Jasvinder Kaur; Ram K. Gupta; Anuj Kumar (Discover Nano, 2024)
Abstract Direct ethanol fuel cells (DEFCs) have been widely considered as a feasible power conversion technology for portable and mobile applications. The economic feasibility of DEFCs relies on two conditions: a notable reduction in the expensive nature of precious metal electrocatalysts and a simultaneous remarkable improvement in the anode's long-term performance. Despite the considerable progress achieved in recent decades in Pt nanoengineering to reduce its loading in catalyst ink with enhanced mass activity, attempts to tackle these problems have yet to be successful. During the ethanol oxidation reaction (EOR) at the anode surface, Pt electrocatalysts lose their electrocatalytic activity rapidly due to poisoning by surface-adsorbed reaction intermediates like CO. This phenomenon leads to a significant loss in electrocatalytic performance within a relatively short time. This review provides an overview of the mechanistic approaches during the EOR of noble metal-based anode materials. Additionally, we emphasized the significance of many essential factors that govern the EOR activity of the electrode surface. Furthermore, we provided a comprehensive examination of the challenges and potential advancements in electrocatalytic EOR. Graphic abstract